Green Marketing, Green Packaging and Green Brand Image Against Repurchase Intention at Greensmart Sidoarjo: Green Marketing, Green Packaging dan Green Brand Image Terhadap Repurchase Intention pada Greensmart Sidoarjo - Zaytun, Anita Al; Sari, Dewi Komala (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of Green Marketing, Green Packaging and Green Brand Image on Repurchase Intention at Greensmart Sidoarjo. This research is a descriptive research using quantitative methods. Sampling in this study was carried out using the Non Probability Sampling technique with the Accidental Sampling method and the number of samples in this study was 150 respondents. Data collection techniques using a questionnaire. This study uses multiple linear regression techniqueby using the SPSS version 20 program to analyze the data accurately. The results, this study has proven that Green Marketing has not an effect on Repurchase Intention, Green Packaging has an effect on Repurchase Intention, and Green Brand Image has an effect on Repurchase Intention at Greensmart in Sidoarjo.